Perencanaan Strategis SI/TI Menggunakan Metode Ward and Peppard pada PT Indomarco Prismatama - Nining Ariati; Ajeng Armadi Rani; Raja Amar Siregar; Yoga Kurniawan; Reza Mahendra (Universitas Maritim AMNI Semarang, 2024)
Modern companies in the digital era face challenges in maximizing the utilization of information systems (IS) to enhance business efficiency and competitiveness. PT Indomarco Prismatama, one of Indonesia's largest retail companies, requires an integrated IS strategic plan to strengthen business processes and optimize information management. This study aims to develop an IS strategic plan for PT Indomarco Prismatama using the Ward and Peppard method, which combines SWOT analysis, PEST analysis, Value Chain analysis, and McFarlan Strategic Grid mapping to identify and assess the company's IS needs and opportunities. Through internal and external environmental analysis, it was found that several business areas require further IS development, including inventory management, customer relations, and supply chain integration. The IS recommendations provided in this study are expected to serve as a foundation for more effective IS development that aligns with the company's business strategies, thereby supporting sustainable growth and increased competitiveness in the retail market.